Differentiating the Persistency and Permanency of Some Two Stages DNA Splicing Language via Yusof-Goode (Y-G) Approach - Mudaber, Mohammad Hassan; Yuhani, Yusof; Mohd Sham, Mohamad (IOP Publishing, 2017)
Predicting the existence of restriction enzymes sequences on the recombinant DNA fragments, after accomplishing the manipulating reaction, via mathematical approach is considered as a convenient way in terms of DNA recombination. In terms of mathematics, for this characteristic of the recombinant DNA strands, which involve the recognition sites of restriction enzymes, is called persistent and permanent. Normally differentiating the persistency and permanency of two stages recombinant DNA strands using wet-lab experiment is expensive and time-consuming due to running the experiment at two stages as well as adding more restriction enzymes on the reaction. Therefore, in this research, by using Yusof-Goode (Y-G) model the difference between persistent and permanent splicing language of some two stages is investigated. Two theorems were provided, which show the persistency and non-permanency of two stages DNA splicing language.